Red-eared slider Trachemys scripta - a new species of herpetofauna of Stavropol region - Mikhail Pavlovich Ilyukh (Наука. Инновации. Технологии)
For the first time in natural conditions of Stavropol region and possibly all Russia the american species - red-eared slider Trachemys scripta which got here is met, most likely, from bondage and successfully got accustomed.